Bearing capacity of perforated offshore foundations under combined loading - Tapper, L (2013)
This thesis presents experimental work and numerical analysis that has been undertaken to assess the bearing capacity of perforated offshore foundations. Perforated foundations may be used to support subsea infrastructure, including as mudmats into which a number of perforations have been made, or as grillages which consist of a series of structurally connected strip footings. Larger gravity base foundations, such as for offshore wind turbines or oil and gas platforms, may adopt a single central perforation. The advantages of using perforated foundations can include reduced material requirements and easier offshore handling as a result of smaller weight and lower hydrodynamic forces during deployment. Limited guidance currently exists for assessing the bearing capacity of these foundation types. Bearing capacity of perforated foundations has been examined in this thesis under conditions of combined vertical, horizontal and moment loading which is typical in offshore settings. Undrained soil conditions have been considered, except for the case of grillages in which drained conditions are often most relevant. Experimental work has included centrifuge testing of ring and square annular foundations on clay, and 1g testing of grillage foundations on sand. Finite element modelling has also been undertaken to assess perforated foundation capacity. A Tresca material subroutine (UMAT) and an adaptive meshing scheme have been developed to improve the accuracy of the finite element analysis carried out. The results showed that perforated foundations can be an efficient foundation solution for accommodating combined loading. As a ratio of their vertical load capacity, perforated foundations may be able to withstand higher moment and horizontal loads compared with unperforated foundations. The experimental and numerical results have been used to develop design expressions that could be employed by practitioners to estimate the vertical and combined load bearing capacity of these foundation types.